Individual investors' satisfaction and loyalty in online securities trading using the technology acceptance model. (6th July 2020) - Nguyen, Hien; Pham, Long; Williamson, Stan; Hung, Nguyen Duy
This research integrates perceived trust, perceived security, perceived privacy, and switching cost into the TAM in order to explain the relationship between customer satisfaction and customer loyalty. This study is one of the first comprehensive and systematic research efforts on the relationship between customer satisfaction and customer loyalty in the online trading setting of Vietnam. Results of this study show that the integrated model demonstrated very high predictive power, explaining more than 64% of the variability of customer loyalty. The study also demonstrates that in Vietnam's online trading setting, perceived trust has positive impacts on perceived ease of use and perceived usefulness; perceived ease of use has a positive impact on perceived usefulness; perceived trust and perceived usefulness have positive impacts on satisfaction; and finally, customer satisfaction has a positive impact on customer loyalty.